Improved Short-Circuit Current Calculation of Doubly Fed Wind Turbines With Uninterrupted Excitation - Yin, Jun (Frontiers in Energy Research, 2021)
With the enlarging scale of a doubly fed induction generator (DFIG) connected to a power system, the influence of short-circuit current on the system relay protection could not be ignored. Setting and configuring relay protection would be affected by an imprecise short-circuit current calculation. However, some existing studies only consider the condition that the input is the Crowbar and the rotor excitation is blocked. China's new network standard requires the output reactive support current of a DFIG and will change the characteristics of short-circuit current. To solve this problem, on the basis of analyzing the characters of the transient equivalent potential of a DFIG, the transient model of a DFIG with uninterrupted excitation is provided. Based on the characteristics of a non-abrupt change of flux linkage and the requirement of a new grid standard reactive support current, the short-circuit current calculation method of a DFIG with uninterrupted excitation is put forward. Based on the real-time digital simulator (RTDS), a digital-analog experimental platform containing the actual control unit of the DFIG converter is founded, the proposed short-circuit current root mean square (RMS) value calculating method is validated.